Risks of a lifetime in construction. Part II: Chronic occupational diseases. Issue 11 (14th August 2014) - Ringen, Knut; Dement, John; Welch, Laura; Dong, Xiuwen Sue; Bingham, Eula; Quinn, Patricia S.
Abstract Background We developed working‐life estimates of risk for dust‐related occupational lung disease, COPD, and hearing loss based on the experience of the Building Trades National Medical Screening Program in order to (1) demonstrate the value of estimates of lifetime risk, and (2) make lifetime risk estimates for common conditions among construction workers. Methods Estimates of lifetime risk were performed based on 12, 742 radiographic evaluations, 12, 679 spirometry tests, and 11, 793 audiograms. Results Over a 45‐year working life, 16% of construction workers developed COPD, 11% developed parenchymal radiological abnormality, and 73.8% developed hearing loss. The risk for occupationally related disease over a lifetime in a construction trade was 2–6 times greater than the risk in non‐construction workers. Conclusions When compared with estimates from annualized cross‐sectional data, lifetime risk estimates are highly useful for risk expression, and should help to inform stakeholders in the construction industry as well as policy‐makers about magnitudes of risk. Am. J. Ind. Med. 57:1235–1245, 2014. © 2014 Wiley Periodicals, Inc.